Web-Based Information System for Monitoring Soil Conditions (Moisture and Temperature) Integrated with IoT - Ahmad Farzi Anwar; M. Husaini; Khairun Nita Aulia (ULTIMATICS, 2026)
Indonesia's agricultural sector faces challenges due to climate change and limited access to accurate, real-time information on soil conditions. Traditional methods relying on visual observation are inefficient and prone to error, which can reduce crop productivity. This research aims to develop a web-based information system integrated with the Internet of Things (IoT) for real-time monitoring of soil moisture and temperature. The system was developed using a Research and Development (R&D) approach with prototyping methodology. The hardware components include an ESP32 microcontroller, a capacitive soil moisture sensor v1.2, and a DS18B20 digital temperature sensor. Sensor data is transmitted to Firebase Realtime Database and displayed via a web interface built with HTML, CSS, and JavaScript. Field trials conducted in Talang Padang village (OKU Selatan) over 7 days demonstrated the system's ability to provide accurate, real-time monitoring. The system includes real-time gauge visualizations, historical graphs, notification features, and exportable sensor logs. Positive responses from farmers indicate the system's potential to support better agricultural decision-making. However, internet dependency and the need for sensor recalibration remain as limitations.